Analisis Perhitungan Pajak Penghasilan 21 terhadap Kinerja Pegawai Tetap di SMP Negeri 2 Cibinong - Nauval Alamsyah Sartono (Departement of Mathematics Education, 2023)
Taxes are dues that must be paid to the state in accordance with applicable regulations. These contributions are mandatory and can be imposed on individuals or entities that are determined as taxpayers. The purpose of this study is to determine the suitability of PPh 21 calculations at SMP Negeri 2 Cibinong with the net method and real calculations and to find out the calculation of PPh 21 on the performance of permanent employees at SMP Negeri 2 Cibinong, it is appropriate and in accordance with Law number 36 of 2008 and Director Regulations General of Taxes Number PER-16/PJ/2016.